Are gritty leaders happier or unhappier? It depends on how prudent they are - Rego, J.; Bluhm, D. J.; Valverde, C.; Pina e Cunha, M. (Group and Organization Management, 2025)
Grit in leaders (and, in general, all employees) typically results in greater success and well-being but also has potential downsides. We propose that gritty leaders also need to be prudent or they may spend excessive time and resources at work, leading to greater work-to-family conflict and, as a result, lower well-being. Findings of two studies support this reasoning. Grittier and imprudent leaders experience greater work-to-family conflict and lower affective well-being, whereas grittier and prudent leaders experience lower work-to-family conflict and greater affective well-being. We therefore conclude that the agentic resource of grit in leaders may be either positively or negatively related to their affective well-being depending on their prudence. Considering that work-to-family conflict and affective well-being are important for the leader’s health and performance, which in turn may influence team/organizational performance, our study contributes to a better understanding of the routes leading to better leadership and team/organizational functioning.